ASSESSING TRADITIONAL MEDICINE, HEALTH LAW, AND GLOBALIZATION IN INDONESIA: TOWARD ACCOUNTABILITY AND SAFEGUARDS - Tengku Keizerina Devi Azwar; Princess Alyssa D. Tee-Anastacio (KANUN:JURNAL ILMU HUKUM, 2025)
Traditional medicine, as part of Indonesia’s healthcare system, is a form of treatment distinct from modern medicine that aims to complement technological advances. This article analyzes changes in health law amid globalization and its relationship to traditional medicine within Indonesia’s legal framework, focusing on Law Number 17 of 2023 and its derivative instruments. This normative legal study emphasizes conceptual and legislative approaches. The findings indicate that regulation of traditional medicine as part of the globalizing health system has been addressed through the Health Law and Government Regulation on Traditional Health Services. However, legal certainty regarding the liability of traditional medicine and the protection of patient rights remains insufficient. Therefore, strengthening regulations, improving supervision, enhancing public education, and establishing a responsive dispute-resolution system are essential to protect patients while ensuring the continuity of traditional medicine. The regulation of traditional medicine in Indonesia possesses specific characteristics that may require special regulations or affirmative action to address liability for errors or shortcomings within the Health Law and related regulations. Consequently, it is necessary to bolster derivative regulations, intensify supervision, expand public education, and implement a responsive dispute-resolution framework to safeguard patients and sustain traditional medicine in the era of globalization. Revising the Health Law and related regulations to reflect the scientific development of traditional medicine and to ensure accountability for medical negligence, surveillance, and patient rights is a strategic step toward clearly delineating accountability mechanisms, operational standards, and patient-protection guarantees.